KUALITAS SANAD HADIS BIRRUL WĀLIDAĪN RIWAYAT ABŪ DĀWŪD - Khairun Nadzirah Binti Abd. Rashid (UIN Sumatera Utara Medan, 2020)
Devoted to both parents (birrul wālidaīn) is a noble practice which is demanded by religion where it is ordered by God as contained in the Koran and Hadith. Those who are devoted to both parents has been promised by God will get peace of life not only in the world but also in the hereafter and he was rewarded by heaven. In determining the quality of the hadith which will be examined from the narrator's side which will determine whether a hadith can be used as evidence or not, i‘tibār activities will be carried out. But before the i‘tibār activity is carried out, the Takhrij Hadith activity is first carried out as a first step of research for the Hadith to be examined, then all the hadiths are recorded and collected for later activities of i‘tibār and tarjamah ar-ruwāh. By doing i‘tibār sanad and tarjamah ar-ruwāh, it will be clearly seen all the paths of the hadith that were studied, as well as the names of the narrators (biographies), the transmission method used by each narrator concerned, and the credibility of the narrators. Through the use of i‘tibār, it is also known that the status of the hadith is entirely seen from the presence or absence of supporters in the form of narrators who have the status of mutabi or shaheed.